Ndlela leyi Shabangu a paluxisaka xiswona vavasati eka matsalwa ya yena ya Xivoni xa Vutomi na Xidawudawu xa Wansati : maendlelo ya feminism - Makhubele, K. (My University, 2013)
Refer to the document
The depiction of women characters in Shabangu's work of Xivoni xa Vutomi and Xidawudawu xa Wansati : a feminist approach.
Thesis (M.A. (African Languages )) --University of Limpopo, 2013
Keywords: Women in literature; Tsonga literature; Women in literature; Feminist literary criticism; Tsonga literature; African literature -- History and criticism